Pendidikan Nilai Keberagaman dalam Membangun Kepribadian Sehat (Studi Deskriptif terhadap Siswa Madrasah Aliyah Darul Arqam Muhammadiyah Garut) - Dewi Sadiah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Potency of the high absorption obtained if learning in effective. Effective learning occurs when students are placed as individual active and direct contact with the subject matter. This research aims to reduce the limitations of the tool (a computer or laptop) and maximizing existing facilities (hand phone) with the aim of achieving effective learning that puts students as subjects of learning. This study is a research field for conducting comparative academic performance of two models of learning. The first learning model is simulation learning and the second model is self-learning via mobile facility. Self-learning materials in this research is the material in the form of video 3GP and transferred to the student’s mobile. The research population is 85 students and a sample taken by 70 students. The data in this study is the performance of students from simulation learning model and self- learning model based 3GP video. Data analysis using Inferential statistical, namely the t-test. Data analysis was performed after the fulfillment of the requirements for normality of data. The results of hypothesis testing obtained the results as following: The value t count bigger than t table (5.957> 2.025). Thus Ha is received and Ho is rejected (significance below or equal to 0.05 so Ha is received). Means that there are significant differences between simulation learning model and self-learning model based 3GP video. Keywords: Learning Media, 3GP Video.